PENGARUH PENGGUNAAN COMPLEMENTARY SPLIT RING RESONATOR (CSRR) DAN U-SLOT DENGAN PENCATUAN PROXIMITY COUPLING PADA ANTENA MIKROSTRIP TRIANGULAR - Silvie Annisa, Maudy; Sandi, Efri; Diamah, Aodah (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2024)
Microstrip antenna is one of the important components in weather radar system, especially in X-band frequency, which requires high performance in terms of gain and bandwidth. This study analyzes the effect of triangular Complementary Split Ring Resonator (CSRR) and U-slot techniques with proximity coupling feeding on the performance of triangular microstrip antenna. The material used is Rogers RT5880 with a dielectric constant of 2.2. The simulation results show that the conventional antenna produces a VSWR value of 1.374, a return loss of -16.039 dB, a bandwidth of 78.707 MHz, and a gain of 10.12 dB. Meanwhile, the antenna modified with CSRR and U-slot and proximity coupling feeding shows improved performance with a VSWR value of 1.495, a return loss of -14.048 dB, a bandwidth of 160.596 MHz, and a gain of 12.09 dB. The addition of a CSRR structure to the groundplane, as well as a U-slot and inset feed to the patch, has proven effective in increasing antenna gain and bandwidth. Therefore, this technique has potential application in weather radar systems to improve signal transmission efficiency and quality.